Preparation Of 11th-Grade Government Institutions/Agencies Accounting Practicum Teaching Materials At Maitreyawira Tanjungpinang Vocational High School - Eren Eren; Anita Anita (Universitas Internasional Batam, 2023)
Coronavirus Disease 2019 (Covid-19) makes people adapt to all aspects of life, including education. Maitreyawira Tanjungpinang Vocational High School began implementing face-to-face learning by tightening health protocols to maintain the effectiveness of teaching and learning activities. The application of learning that is carried out face-to-face certainly requires teaching materials. The problem experienced by the school at this time is that they need more time and space to prepare teaching materials for the new school year, specifically 2022/2023. Until now, teachers have only used printed books corresponding to the syllabus in the teaching process. This teaching method is challenging for teachers and not attractive to students accustomed to using information technology during Covid-19. Thus, this community service activity aims to prepare engaging teaching materials for the 11th-grade Government Institutions/Agencies Accounting Practicum at Maitreyawira Tanjungpinang Vocational High School. The primary and secondary data and information needed in this preparation are collected through interviews and literature studies. Stages of implementation of teaching materials preparation activities starting from preparation to assessment and reporting. The outputs of the activities are a learning module consisting of eight chapters with practice questions and answer keys, eight PowerPoints, and eight YouTube videos. Based on feedback from the teacher of related subjects through questionnaire, the teaching materials compiled will be beneficial for the teaching and learning process. Teaching materials are challenging to implement in the long term if there are no periodic adjustments to the core and basic competencies, which are constantly updated following the curriculum and the new school year. Therefore, the suggestion for similar projects in the future is to evaluate and adjust the teaching materials that have been prepared previously following the update of core and basic competencies.